Surface magnetic contribution in zinc ferrite thin films studied by element-And site-specific XMCD hysteresis-loops - Mendoza Zélis, Pedro (2016)
Element-And site-specific magnetic hysteresis-loops measurements on a zinc ferrite (ZnFe2O4) thin film were performed by X-ray magnetic circular dichroism. Results show that iron in octahedral and tetrahedral sites of spinel structure are coupled antiferromagnetically between them, and when magnetic field is applied the magnetic moment of the ion located at octahedral sites aligns along the field direction. The magnetic measurements reveal a distinctive response of the surface with in-plane anisotropy and an effective anisotropy constant value of 12.6 kJ/m3. This effective anisotropy is due to the combining effects of demagnetizing field and, volume and surface magnetic anisotropies KV =3.1 kJ/m3 and KS =16 μJ/m2.